Rekrutmen Calon Legislatif Muda Partai Golongan Karya Untuk Dewan Perwakilan Rakyat Republik Indonesia Periode 2019-2024 - Delya Afrida Sari; Wawan Budi Darmawan; Firman Manan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to describe the recruitment of young legislative candidates for the Golkar Party in the 2019 elections. The problem is focused on how the recruitment of young legislative candidates is carried out by the Golkar party. In order to approach this problem, the theory of political recruitment from Michael Rush and Philip Althoff was used. The data were collected through interviews and analyzed qualitatively. The type of research used is descriptive which intends to provide the results of exploration or exploration of information on the research objectives. This study concludes that the political recruitment of young golkar party legislative candidates for the House of Representatives of the Republic of Indonesia for the 2019-2024 period includes five activity processes, namely: supply and demand, agency, criteria, control and demand.